Uterine artery diastolic notch and S/D ratio as early markers for predicting neonatal morbidity in patients with hypertensive disorders of pregnancy - Gheewala, Amisha; Patel, Priyanka; Barvaliya, Parth; Jariwala, Nidhi; Savaliya, Bhakti; Nayak, Krutik (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Hypertensive disorders of pregnancy (HDP) affect 5-10% of pregnancies globally and are major contributors to neonatal morbidity. This study evaluated the correlation between Doppler indices of the uterine (UtA), umbilical (UA), and middle cerebral (MCA) arteries and fetal outcomes in HDP. Methods: This prospective observational study, conducted at a tertiary care center in south Gujarat from September 2023 to February 2025, enrolled 138 pregnant women with a gestational age beyond 28 weeks diagnosed with HDP. Doppler indices, including the systolic/diastolic (S/D) ratio, resistance index (RI), and pulsatility index (PI), were recorded for the UtA, UA, and MCA. Results: Preeclampsia was the most frequent diagnosis (53.6%). The UtA S/D ratio and the presence of a diastolic notch were significantly associated with neonatal morbidity (p=0.01), whereas UtA PI and RI were not significant predictors. All UA and MCA indices showed significant correlations with adverse outcomes (p=0.01). Notable outcomes included 63.04% low birth weight, 57.25% NICU admissions, and 10.8% neonatal deaths. The UtA notch achieved a diagnostic accuracy of 75.36%. Conclusions: Abnormal Doppler indices, specifically in the UA and MCA, are reliable markers for predicting neonatal risk. Routine triple-vessel Doppler screening is recommended for early risk stratification and timely intervention in HDP.